Proceso de atención de enfermería en adulto mayor con insuficiencia cardiaca congestiva. - Salinas Millingalli, Josselyn Sadith (2021)
Heart failure is a clinical syndrome due to the functional inability of the heart to pump blood to different tissues and organs, there are different risk factors among which we have: high blood pressure, sedentary lifestyle, obesity, smoking, among others. According to the World Health Organization (WHO), cardiovascular diseases are the leading cause of death worldwide with 31% representing 17.7 million people (WHO, 2017). Enrique Ruiz (president of the South American Society of Cardiology) points out that in Ecuador there is 14% of the population with heart disease, calculating some 199 thousand people with heart failure (Ruiz, 2018). This disease is characterized by a variety of symptoms such as such as dyspnea. edema, fatigue, tachycardia, cough and wheezing. Concluding that Congestive Heart Failure is a chronic disease that needs life-long control, however, with medical treatment, a proper lifestyle, and a correct diet, the signs and symptoms are reduced, preventing the disease from progressing progressively. The objective of this clinical case study is to analyze the application of the nursing care process in a 79-year-old patient with congestive heart failure, through the use of tools applied by the nursing staff such as NANDA labels, NOC results, and interventions. NIC for the correct follow-up and observation of the patient; In addition, different nursing models were used, such as Marjory Gordon with her 11 functional patient patterns.